An Ottoman cosmography - Kâtib Çelebi, 1609-1657. (Leiden ; Boston)
xiii, 694 sayfa
Keywords: “Cihānnümā is the summa of Ottoman geography and one of the axial texts of Islamic intellectual history. Kātib Çelebi (d. 1657) sought to combine the Islamic geographical tradition with the new European discoveries, atlases and surveys. His cosmography included a comprehensive description of the regions of the world, extending westward from Japan and as far as the eastern Ottoman provinces. Ebū Bekr b. Behrām ed-Dimaşḳī (d. 1691) continued with a survey of the Arab countries and the remaining Ottoman provinces of Anatolia. İbrāhīm Müteferriḳa combined the two, with additional notes and maps of his own, in one of the earliest Ottoman printed books, Kitāb-ı Cihānnümā (1732). Our translation includes the entire text of Müteferriḳa's edition, distinguishing clearly between the contributions of the three authors. Based on Kātib Çelebi's original manuscript we have made hundreds of corrections to Müteferriḳa's text. Additional corrections are based on comparison with Kātib Çelebi's Arabic, Persian, Turkish, Latin and Italian sources.“ --